2008
DOI: 10.1179/174329307x249289
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of MIG welding stability in pure Ar shielding gas using small amount of oxygen and coaxial hybrid solid wire

Abstract: Metal inert gas/metal active gas (MIG/MAG) welding is generally used in many fields because of its high efficiency. Metal inert gas welding is expected but has not been used in pure Ar shielding gas because of arc instability. Shielding gas including O 2 or CO 2 has been used to secure the arc stability. However, these gases cause the quality of joints to deteriorate. Therefore, the authors have investigated the case of instability using a high speed video camera system to achieve a stable MIG welding in pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…The welding parameters affect the MDT mode as well as the weld quality in P-GMAW [1,2]. Nakamura et al [3] used a high speed video camera system to study the stability of GMAW welding process. The observation showed that the unstable welding behavior was due to the instability of a column of metal droplet generated at the wire tip.…”
Section: Introductionmentioning
confidence: 99%
“…The welding parameters affect the MDT mode as well as the weld quality in P-GMAW [1,2]. Nakamura et al [3] used a high speed video camera system to study the stability of GMAW welding process. The observation showed that the unstable welding behavior was due to the instability of a column of metal droplet generated at the wire tip.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ar-GMA welding using a conventional commercially available solid wire is not used because of arc instability. 1,2) The major cause of arc instability in Ar-GMA welding is the long column of liquid molten metal (CLM) generated at the wire tip 1,2) The irregular movement of the CLM and frequent short-circuit makes the arc unstable. As a result, the welding becomes unstable due to the large variation of the welding current and wire extension.…”
Section: Introductionmentioning
confidence: 99%
“…To stabilize the Ar-GMA welding, the CLM must be kept short. We previously developed a coaxial multi-layer solid wire (CMS wire) 1,2) that has a double structure consisting of a center wire (center area) and a hoop (outer area), which differ in composition.…”
Section: Introductionmentioning
confidence: 99%
“…Coaxial hybrid solid (CHS) wires have been developed to carry out stable MIG welding in pure Ar shielding gas 1,2) . The characteristics of the weld metal can be improved using the MIG welding in pure Ar shielding gas (Ar-MIG welding) since the amount of oxygen in weld metal, which deteriorates the characteristics of weld metal, decreases 3) .…”
Section: Introductionmentioning
confidence: 99%
“…CHS wires have been developed to shorten this CLM 1,2) . The composition of the inner and outer parts were selected so that the amount of melting in the inner part became greater than that of the outer part.…”
Section: Introductionmentioning
confidence: 99%